The Association Between Prebooster Vaccination Antibody Levels and the Risk of Severe Acute Respiratory Syndrome Coronavirus 2 Infection. (11th November 2022) - Barda, Noam; Canetti, Michal; Gilboa, Mayan; Asraf, Keren; Indenboim, Victoria; Weiss-Ottolenghi, Yael; Amit, Sharon; Zubli, Daniel; Doolman, Ram; Mendelson, Ella; Freedman, Laurence S; Kreiss, Yitshak; et al.
Abstract: The correlation between anti–severe acute respiratory syndrome coronavirus 2 antibody levels and infection was reported. Here, we estimated the role of pre–fourth dose levels using data from 1098 healthcare workers. The risk of infection was reduced by 46% (95% confidence interval, 29%–59%) for each 10-fold increase in prebooster levels. Prebooster antibody levels could be used to optimally time boosters.